Field reports form for submitting seasonal observations of Iowa birds, summer 1995, Mark Proescholdt - Proescholdt, Market al (1995)
An annotated list of birds sighted by Mark Proescholdt and others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1995. Epson - sheet feed/flatbed